Pustulosis Eksantematosa Generalisata Akut - Pandaleke, Thigita A.; Pandaleke, Herry E. J. (UNIVERSITAS SAM RATULANGI, 2017)
Abstract: Acute generalized exanthematous pustulosis (AGEP) is a rare skin disorder commonly caused by drugs. Skin lesions can occur within 1-2 days after drug consumption in the form of sterile pustules on erythematous skin base and accompanied by fever. Mortality rate reaches 5%, especially in elderly patients who have significant comorbid factors. Etiopathogenesis is still unclear, presumed to be drugs (beta-lactam and macrolide antibiotics), although it can also be caused by infection and hypersensitivity to mercury. Incidence of AGEP approximately 1-5 million cases per year. It can occur at all ages, and more common in females than in males. The typical clinical features are non-follicular pustules erupting on erythematous skin and fever. In most cases, the skin lesions begin from the face or intertriginous areas and then within a few hours the pustules will spread to the lower trunk and limbs, accompanied by mild burning and minimal itching complaints. Histopathology provides an overview of sub-corneal spongiform and or intraepidermal pustules which are often accompanied by edema of the dermal papilla and perivascular neutrophil infiltration along with exocytosis of eosinophils. The management of AGEP is to stop the suspected drugs, continued with symptomatic therapy. Prognosis PEGA is generally good, unless secondary infection is present.Keywords: AGEP, sterile pustulesAbstrak: Pustulosis eksantematosa generalisata akut (PEGA) merupakan kelainan kulit langka yang umumnya disebabkan oleh obat. Lesi kulit dapat timbul dalam 1-2 hari setelah mengonsumsi obat berupa pustul steril di atas dasar kulit yang eritematosa dan disertai dengan keluhan sistemik berupa demam. Angka kematian akibat PEGA mencapai 5% terutama pada pasien usia lanjut dengan faktor komorbid yang jelas. Etiopatogenesis PEGA belum jelas, diduga obat (antibiotik golongan beta laktam dan makrolid), meskipun juga dapat diakibatkan oleh infeksi dan hipersensitivitas terhadap merkuri. Insiden terjadinya PEGA kurang lebih 1-5 juta kasus pertahun, dapat terjadi pada semua usia, dan lebih banyak ditemukan pada perempuan dibandingkan laki-laki. Gambaran klinis khas PEGA ialah pustul-pustul non-folikular yang timbul diatas kulit yang eritematosa dan disertai demam. Pada kebanyakan kasus keluhan kulit diawali dari area wajah atau lipatan kemudian dalam beberapa jam pustul akan menyebar ke trunkus dan ekstremitas bagian bawah, kadang disertai rasa terbakar ringan dan gatal minimal. Gambaran histopatologik menunjukkan pustul spongiformis subkorneal dan atau pustul intraepidermal disertai dengan edema pada papila dermis dan infiltrasi neutrofil perivaskular bersamaan dengan eksositosis eosinofil. Penatalaksanaan PEGA ialah menghentikan obat yang dicurigai, dilanjutkan dengan terapi simptomatik. Prognosis umumnya baik dan dapat sembuh sendiri, kecuali bila terdapat infeksi sekunder.Kata kunci: PEGA, pustul steril